Rethinking Digital Pedagogy: Unveiling the Hidden Complexities of Teaching Islamic Values to Special Needs Students - Almi Novita; Annisaul Fathirah (Zamzami Scholar Publishing, 2026)
This study investigates the architecture of an online Islamic education learning system for children with special needs at Sekolah Kreatif SD Muhammadiyah 1 Menganti. It applies a qualitative approach with a case study design, and empirical data collection focuses on virtual observation, in-depth interviews, and documentation review. The research findings prove the application of adaptive digital pedagogy through planned instructional differentiation. This approach maintains the equivalence of material substance for regular students by adjusting the conceptual complexity and simplifying evaluation standards. The successful internalization of spiritual values is built through the distribution of periodic worksheets, intensive virtual communication interventions, and task completion guidance based on kinetic movement stimulation. The implementation of this virtual ecosystem underscores the urgency of synergistic collaboration among educators, special assistant teachers, and parents as the primary guides in the home environment. This instructional design constellation offers an essential managerial prototype for similar institutions to ensure the fulfillment of adaptive and proportional religious education accessibility.